Impact of community participation in adaptive wildlife resources management at Mole National Park, Ghana - Tiimub, Benjamin Makimilua; Gbolo, Braimah; Tiimob, Richard Wonnsibe; Tiimob, Ernestina Laatman; Kumedzro, Vida; Tiimob, Elisha (Goodwood Publishing, 2019)
Purpose: Wildlife resources constitute indispensable nature’s strongholds for human livelihoods strategies in forest, savanna zones across Ghana and the worldwide although, it often engendered conflicts. Impact of community participation on adaptive wildlife resources management was strategically assessed at Mole National Park. Research methodology: 60 randomly selected park environs residents were interviewed for valid responses using semi-structured questionnaires. Findings: High wildlife products demand has transformed bush meat into lucrative business through poaching by thousands of youths and adults, causing habitat destruction and sharp wildlife population decline. Hunters, poachers, middlemen, restaurant operators constituted game-trade-market-value chain. Limitations: Funding subjectivity reduced scope of the study to only few communities in dry season. Temptation to reject the questionnaires on suspicion of force evacuation plots against some park adjoining villages was later refuted. Hence, recovery rate was 100%. Contribution: We recommend that Wildlife Division of the Forestry Commission should strengthen synergies on community participation in adaptive wildlife management by coopting educational interventions that positively influence indigenous behaviors through seminars, workshops, face-to-face interactions. This will better define the rights, roles, responsibilities of key partners towards resolving communal wildlife conflicts. Keywords: Community participation, Wildlife management, Park sustainability, Poaching, Game-trade-market-value chain